Studies on antibiotic resistance profiles of thermotolerant Escherichia coli and multiple antibiotic resistance index of different water sources - Varghese, Mabel; Roymon, M G (Recent Research in Science and Technology, 2013)
The rationale behind this study was that no clear data from Durg District is available on the antibiotic resistance profiles of E. coli, the most common pathogen of both humans and animals. Water being one of the most prevalent routes of transmission of E. coli, the present study aimed at isolation and characterization of the same from widely used water sources of Durg-Bhilai region. Thermotolerant E. coli (n=50) were isolated from municipal water, ground water, lake (Talpuri Talab), and river Shivnath. Multiple antibiotic resistance (MAR) indexing was performed using antibiotics viz. amoxicillin, chloramphenicol, co-trimoxazole, ceftriaxone, ciprofloxacin, cephotaxime, nalidixic acid, gentamycin and tetracycline. 85.4% of isolates showed resistance to 2 or more antibiotics. Resistance to three or more antibiotics (multidrug resistance) was shown by 24.4% of isolates. Plasmid bands ranging in size from 0.5 kb – 35 kb were present in 35 out of 50 isolates. Multiple plasmids were shown in 6 isolates. MAR index of isolates ranged from 0.11 to 0.55. 61% of isolates in this study had an index of 0.22, 14.63% had 0.44, 7.23% had 0.33 and 2.44% had 0.55. A high index of 0.79 was shown by River Shivnath followed by 0.2 by Talpuri Talab. The MAR index >0.2 is considered to originate from high risk source of contamination. High MAR indices of individual isolates and sampling sites in Durg-Bhilai region showed that water sources are contaminated with antibiotic resistant E. coli arising from high risk sources of contamination.